Estudo do feromônio de Opsiphanes invirae (Hubner, 1818) (Lepidoptera: Nymphalidae) - Chagas , Keciane Mesquita das (2018)
DUE THE SYSTEM DOES NOT RECOGNIZE EQUATIONS AND FORMULA, THE ABSTRACT CAN BE FOUND IN THE PDF FILE.